Effects of Dietary Lonicera flos and Sucutellaria baicalensis Mixed Extracts Supplementation on Reproductive Performance, Umbilical Cord Blood Parameters, Colostrum Ingredients and Immunoglobulin Contents of Late-Pregnant Sows - Chengkun Fang; Xiaopeng Tang; Qingtai Zhang; Qifang Yu; Shengting Deng; Shusong Wu; Rejun Fang (Animals, 2024)
The present study aimed to determine the effects of dietary Lonicera flos and Sucutellaria baicalensis mixed extract (LSE) supplementation during the late-pregnancy period on the reproductive performance, umbilical cord blood hematological parameters, umbilical cord serum biochemical parameters, immune indices, hormone levels, colostrum ingredients, and immunoglobulin contents of sows. A total of 40 hybrid pregnant sows were randomly assigned to the control group (CON; sows fed a basal diet) and LSE group (LSE; sows fed a basal diet supplemented with 500 g/t PE). The results indicated that dietary LSE supplementation significantly increased (p < 0.05) the number of alive and healthy piglets and the litter weight at birth, and significantly increased (p < 0.05) the platelet counts in umbilical cord blood. Dietary LSE supplementation significantly increased (p < 0.05) the levels of prolactin (PRL) and growth hormone (GH), and the content of interleukin 2 (IL-2) in umbilical cord serum. Moreover, immunoglobulin A (IgA) and immunoglobulin M (IgM) in the colostrum were increased with PE supplementation (p < 0.05). In conclusion, dietary LSE supplementation in late-pregnancy sows could improve reproductive performance and colostrum quality, and could also regulate the levels of reproductive hormone in umbilical cord serum.